2011
DOI: 10.21608/ejar.2011.175645
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and Lethal Effects of the Entomopathogenic Nematodes on the Peach Fruit Fly, Bactrocera Zonata (Saunders) and the Cucurbit Fruit Fly, Dacus Ciliatus (Loew) (Diptera : Tephritidae)

Abstract: Laboratory experiments were performed to evaluate the pathogenic and lethal effects of the entomopathogenic nematodes Hb (Heterorhabditis bacteriophora Poinar) and Sc (Steinernema carpocapsae All strains) on the full grown larvae, newly formed pupae and seven days old adults of the peach fruit fly, Bactrocera zonata and the cucurbit fly, Dacus ciliatus. Mortality rates ranged from 9.3 to 42.7%, 12.7 to 52.3 % for the full grown larvae of both B. zonata and D. ciliatus treated by Sc nematode, respectively, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Our results indicated that the larval stage was the most susceptible stage, which is in agreement with findings from numerous reports 16,17,39,39,40,59 . These studies showed that the larval stage was found more vulnerable than the pupae stage.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results indicated that the larval stage was the most susceptible stage, which is in agreement with findings from numerous reports 16,17,39,39,40,59 . These studies showed that the larval stage was found more vulnerable than the pupae stage.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that the larval stage was the most susceptible stage, which is in agreement with findings from numerous reports. 16,17,39,39,40,59 These studies showed that the larval stage was found more vulnerable than the pupae stage. In accordance with our findings, Gul et al 16 found that larvae of B. zonata were more susceptible than pupae when exposed to different fungi (B. bassiana, M. anisopliae and Isaria fumosorosae).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations